Pembuatan dan Pemanfaatan Larutan Multiguna Eco Enzyme sebagai Upaya Reduksi Limbah Organik di Kampoeng Kuliner Makassar: Production and Aplication of Eco Enzyme Multipurpose Solutions as an Effort for Organic Waste Reduction of Kampoeng Kuliner Makassar - Andi Zulfikar Syaiful; Muh. Fikruddin; Ridwan Ridwan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Kampoeng Kuliner Makassar (KKM) is one of the MSMEs in the culinary field in Makassar. KKM produces about 25 kg/day of organic waste, mainly fruit and vegetable. This community partnership program is a form of transfer of knowledge and technology fermentation in organic waste treatment, which aims to assist KKM partners in processing fruit and vegetable peel waste into eco-enzyme which is then used as a multipurpose cleaning solution according to KKM needs. This activity consists of a focus discussion group (FGD), counseling, making and harvesting eco enzyme, and its application in the restaurant as a multipurpose cleaning solution. Paired t-test results of participants' pre-test and post-test showed a significant increase (p-value < 0.001) in participants' knowledge about various aspects of eco-enzyme. The participants' skills are improved through independent practice so that all participants can produce good quality eco enzymes. Eco-enzyme has been used as a cleaning and disinfection agent, such as washing agents for food, tableware, and cooking utensils; kitchen and bathroom cleaners at KKM. After this community partnership program, it is hoped that KKM can become a place to promote a healthy lifestyle with minimal waste.